The Drosophila DAXX-Like Protein (DLP) Cooperates with ASF1 for H3.3 Deposition and Heterochromatin Formation. - Fromental-Ramain, C.; Ramain, P.; Hamiche, A. (Molecular and Cellular Biology, 2017)
Histone variants are nonallelic isoforms of canonical histones, and they are deposited, in contrast to canonical histones, in a replication-independent (RI) manner. RI deposition of H3.3, a histone variant from the H3.3 family, is mediated in mammals by distinct pathways involving either the histone regulator A (HIRA) complex or the death-associated protein (DAXX)/?-thalassemia X-linked mental retardation protein (ATRX) complex. Here, we investigated the function of the Drosophila DAXX-like protein (DLP) by using both fly genetic approaches and protein biochemistry. DLP specifically interacts with H3.3 and shows a prominent localization on the base of the X chromosome, where it appears to act in concert with XNP, the Drosophila homolog of ATRX, in heterochromatin assembly and maintenance. The functional association between DLP and XNP is further supported by a series of experiments that illustrate genetic interactions and the DLP-XNP-dependent localization of specific chromosomal proteins. In addition, DLP both participates in the RI deposition of H3.3 and associates with anti-silencing factor 1 (ASF1). We suggest, in agreement with a recently proposed model, that DLP and ASF1 are part of a predeposition complex, which is recruited by XNP and is necessary to prevent DNA exposure in the nucleus.